Reinterpreting English Textbooks Taks and Activities for The Merdeka Curriculum Context - Nursyahrifa Nursyahrifa; Jufrizal Jufrizal (Indonesian Journal of Educational Studies, 2025)
The transition from Kurikulum 2013 to the Merdeka Curriculum has inevitably required changes in certain aspects of English language teaching and learning, including textbook use. Although new versions of English textbooks have been published to meet the needs of the new curriculum, important questions arise regarding the continued use and relevance of older English textbooks designed under 2013 Curriculum. This study aims to evaluate whether Pathway to English and Bahasa Inggris for Grade X Curriculum 2013 based-textbooks, can still contribute as learning resources within the Merdeka Curriculum context, particularly in terms of their tasks and activities. Developed from an earlier investigation conducted in 2019, this study reinterprets the earlier textbook evaluation findings to assess their alignment with the dimensions of Profil Pelajar Pancasila. Using a descriptive qualitative approach, the study employed a three-step reinterpretative procedure that included reframing the criteria, reinterpreting the 2019 findings in relation to the Merdeka Curriculum, and assigning new scores with supporting descriptions. The reinterpretation focused on five dimensions of Profil Pelajar Pancasila: Independence (mandiri), creative (kreatif), collaboration (gotong royong), and global citizenship (berkebinekaan global). Findings indicate that both Pathway to English and English Subject for Grade 10 can still support the implementation of the Merdeka Curriculum, although requiring certain adaptations and supplementation